The Emotion Regulation Roots of Job Satisfaction - Madrid, Hector P.; Barros, Eduardo; Vasquez, Cristian A. (Frontiers in Psychology, 2020)
Job satisfaction is a core variable in the study and practice of organizational psychology because of its implications for desirable work outcomes. Knowledge of its antecedents is abundant and informative, but there are still psychological processes underlying job satisfaction that have not received complete attention. This is the case of employee emotion regulation. In this study, we argue that employees’ behaviors directed to manage their affective states participate in their level of job satisfaction and hypothesize that employee affect-improving and -worsening emotion regulation behaviors increase and decrease, respectively, job satisfaction, through the experience of positive and negative affect. Using a diary study with a sample of professionals from diverse jobs and organizations, for the most part, the mediational hypotheses were supported by the results albeit a more complex relationship was found in the case of affect worsening emotion regulation. This study contributes to expanding the job satisfaction and emotion regulation literatures and informs practitioners in people management in organizations about another route to foster and sustain positive attitudes at work.